Self-Activity Among Internal Department Supervisors - Al-Mayahy, Rawaa Jaafar Abd; Al-Anzi, Hussein Karim Mohammed (Universitas Muhammadiyah Sidoarjo, 2026)
The current research aims to identify the level of self-activity and reveal the statistical significance of differences in the level of self-activity according to the two gender variables (male-female) among a sample of male and female supervisors in the Department of Internal Affairs at Wasit University. The research sample consisted of (150) male and female supervisors who were selected using stratified random sampling. To achieve this, the researchers developed a self-activity scale based on the theory of (Roon kurtus, 2012) and consists of (30) items distributed towards three dimensions: (mental activity, emotional activity, physical activity). After that, the research instrument was applied and the psychometric properties of the scale were tested for validity and reliability. Reliability was extracted in two ways: Cronbach's alpha and the test-retest method. The scale's reliability using the test-retest method was (0.86), while the reliability using Cronbach's alpha was (0.83). The research results showed that the supervisors of the internal departments enjoy self-activity and a positive attitude in their job performance, and there are no statistical differences according to gender between males and females. In light of the results shown, the researchers presented a number of recommendations and suggestions. Highlights: Supervisors demonstrated high scores across cognitive, emotional, and physical dimensions. Measurement results exceeded the predefined hypothetical benchmark. Male and female groups showed comparable patterns in assessed attributes. Keywords: Self-Activity, Internal Department Supervisors, University Administration, Gender Differences